2007
DOI: 10.1136/bmj.39272.581736.55
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for treatment of acute diarrhoea in children: randomised clinical trial of five different preparations

Abstract: Objective To compare the efficacy of five probiotic preparations recommended to parents in the treatment of acute diarrhoea in children.Design Randomised controlled clinical trial in collaboration with family paediatricians over 12 months. Setting Primary care.Participants Children aged 3-36 months visiting a family paediatrician for acute diarrhoea.Intervention Children's parents were randomly assigned to receive written instructions to purchase a specific probiotic product: oral rehydration solution (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
195
1
18

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(227 citation statements)
references
References 32 publications
(31 reference statements)
8
195
1
18
Order By: Relevance
“…The proposed health benefits include reduction of intestinal infection risk, allergies, and atopic eczema (6,7) and relief from symptoms of inflammatory bowel disease (IBD) (8). However, placebo-controlled cross-over studies to scientifically support these health claims have shown different success rates (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…The proposed health benefits include reduction of intestinal infection risk, allergies, and atopic eczema (6,7) and relief from symptoms of inflammatory bowel disease (IBD) (8). However, placebo-controlled cross-over studies to scientifically support these health claims have shown different success rates (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Isolaruri et al 1994 (26) observed that the mean duration of diarrheoa was significantly lower in probiotics treated group (1.4 day) compared to yoghurt treated group (2.4 days). While with use of probiotics Billoo et al 2000 (27) , Jobst Henker et al (21) , Enduardo et al (22) Roberto Berni Canani et al (28) and Khanna et al 2000 (23) observed that the mean duration of diarrhoea was 3.6 days, 2.5 days, 58.5 hours, 78.5 hours and 58.78 hours respectively. Similarly Szajewska H. et al 2006; (29) observed that probiotics use were significantly reduced the duration of diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…L. acidophilus has been reported to increase gastrointestinal tract resistance to bile, acid pH, and digestive enzymes (Collado et al, 2009). L. rhamnosus has been demonstrated to rotavirus diarrhea in children (Vanderhoof et al, 1999;Guandalini et al, 2000;Canaani et al, 2007), and L. plantarum, which is present in fermented food products, such as, Korean kimchi, helps antimicrobials survive in the human gastrointestinal tract (Nybom et al, 2008;Bixquert Jiménez, 2009;Bested et al, 2013).…”
Section: Discussionmentioning
confidence: 99%